2019
DOI: 10.1002/cbic.201900116
|View full text |Cite
|
Sign up to set email alerts
|

Phenazine Antibiotic‐Inspired Discovery of Bacterial Biofilm‐Eradicating Agents

Abstract: Bacterial biofilms are surface‐attached communities of slow‐growing and non‐replicating persister cells that demonstrate high levels of antibiotic tolerance. Biofilms occur in nearly 80 % of infections and present unique challenges to our current arsenal of antibiotic therapies, all of which were initially discovered for their abilities to target rapidly dividing, free‐floating planktonic bacteria. Bacterial biofilms are credited as the underlying cause of chronic and recurring bacterial infections. Innovative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 148 publications
(418 reference statements)
1
18
0
Order By: Relevance
“…Of those, halogenated quinoline-3 (Figure 12) completely eradicated S. epidermidis biofilms at only 3.0 μM, while halogenated quinoline-4 eradicated (Figure 12) E. faecium biofilm at just 1.0 μM (Basak et al, 2015, 2016). The potential of phenazines as biofilm eradication agents was comprehensively reviewed by the same authors recently (Huigens et al, 2019).…”
Section: Phenazines and Quinolinesmentioning
confidence: 99%
“…Of those, halogenated quinoline-3 (Figure 12) completely eradicated S. epidermidis biofilms at only 3.0 μM, while halogenated quinoline-4 eradicated (Figure 12) E. faecium biofilm at just 1.0 μM (Basak et al, 2015, 2016). The potential of phenazines as biofilm eradication agents was comprehensively reviewed by the same authors recently (Huigens et al, 2019).…”
Section: Phenazines and Quinolinesmentioning
confidence: 99%
“…In our previous work, we have shown that phenazine derivative phenazine #14 specifically disrupted the Hsp27/eIF4E interaction, increased apoptosis, and decreased tumor growth [ 15 ]. The family of heterocyclic nitrogenous phenazine molecules have been originally extracted [ 32 ] and used as antibiotic [ 33 ], antimalarial [ 34 ], and anticancer agents [ 35 ] with limited side effects on healthy tissues [ 36 ]. 2,3-Dialkoxyphenazine lipidic derivatives have shown anticancer activities on pancreatic cancer cell lines [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The collection of halogenated phenazine and quinoline compounds tested in this study originated by probing pyocyanin, a compound produced within the natural setting through bacterial competition. Pyocyanin, a phenazine compound produced by Pseudomonas aeruginosa and the presumed compound credited with outcompeting Staphylococcus aureus in the context of cystic fibrosis lung infections, served as the base structure used to initiate this exploration [40]. Halogenated phenazine analogue [42].…”
Section: Discussionmentioning
confidence: 99%